Preparation and Study Some Properties of Ferrite Nanoparticles(CuxAl0.3-xNi0.7Fe2O4) - Al- Saadi, Tagreed M.; Kadhim, Shaimaa A. (Iraqi Journal of Science, 2024)
The current study includes the preparation of CuxAl0.3-xNi0.7Fe2O4 ferrite nanoparticles where: x = 0, 0.05, 0.1, 0.15, 0.2, 0.25, and 0.3 using the auto combustion method (sol-gel). The citric acid was used as fuel for auto combustion. The X-ray diffraction (XRD) test showed an increase in the crystal lattice constant, which is of face-centered cubic (FCC) structure. Field Emission Scanning Electron Microscopy (FE-SEM) showed that the compound has apparent porosity; its grains are spherical or semi-spherical and within the nanoscale. The Energy-Dispersive X-ray spectroscopy (EDX) proved the presence of all the elements involved in the preparation of the compound, and there are no other elements, which means that it is of high purity. The vibrating sample magnetometer (VSM) showed that the hysteresis loop is small and narrow, meaning the wasted energy is as little as possible. In addition, it was found that the compound has good sensitivity to NO2 gas.